Multibeam bathymetry processed data (Reson SeaBat T50 entire dataset) of RV SANNA during cruise SANNA_2020-07 (Hidden Habitats), Davis Strait - Diana W Krawczyk (PANGAEA, 2025)
High-resolution multibeam data were collected in offshore Disko region as part of the extquotesingleHidden Habitats extquotesingle project with Greenlandic RV Sanna (July 2020). The goal of the project was to explore benthic habitats, in particular vulnerable marine ecosystem species in the unique Arctic area characterized by extreme underwater slopes and boundary between geological units. Data were acquired with hull-mounted Teledyne system SeaBat T50-Extended Range (max. 1000 m) operated at 180 kHz. Positioning and movements of the vessel were obtained from the Applanix POS MV Surfmaster receiving data from an Integrated Motion Unit and two Trimble GNSS antennas. The accuracy of the observations is generally within 0.5 to 2 m horizontally and up to 0.03 degrees roll, pitch, and heading of the vessel. The bathymetry data were SVP-corrected and cleaned using PDS software, and were gridded at 15 x 15 m resolution. Tide correction was not applied.